Influence of natural smoke vent opening in stairway of multistorey building - Nurud Suria, Suhaimi; Sa'ari, Mustapha; Abdullah, I.; Normariah, A.; Mohd Rafee, Baharudin (IOP Publishing Ltd, 2019)
Stairway used as an escape as well as firefighter's route during evacuation. In addition, stairway connecting different floors of a building and becomes a path for the smoke spread in fire event. In a building, every escape route should be installed with smoke control system to ensure the prevention of dangerous smoke accumulation at those areas. The fire perimeter in terms of heat output and smoke generation is highly depends on building occupancy and the efficacy of smoke confinement may have a great challenge. In this paper, numerical simulations were conducted to study the efficacy of natural smoke vent to confine fire-induced smoke transportation in the stairways of multi-storeys buildings. The simulation used Fire Dynamic Simulator (FDS) was conducted on a full-scale building where the influences of smoke vent opening at different fire size were discussed. When the value of heat release rate (HRR) were kept constant, the different vent's size opening had a different influence on the efficacy of smoke vent and an appropriate opening size was obtained and proposed for further action. The finding of this study can assist the fire engineer to ensure that the smoke vent installation play a good role in confinement of smoke diffusion.